ChemInform Abstract: Two Crown‐Ether‐Coordinated Caesium Halogen Salts. Issue 28 (15th July 2014) - van Well, Natalija; Klein, Christian; Ritter, Franz; Assmus, Wolf; Krellner, Cornelius; Bolte, Michael
Abstract Single crystals of [Cs2Br2(18‐crown‐6)2 (H2O)2]·2H2O (I) are grown from an aqueous solution of CsBr and 18‐crown‐6 in a 1:1 molar ratio.